MODEL BISNIS ALUMNI PONDOK PESANTREN - Hari Setiadi (Universitas Garut, 2023)
This paper aims to Pondok Pesantren is a traditional educational institution in Indonesia which has an important role in shaping the character and giving religious education to the students (students). Apart from giving religious education, Islamic boarding schools also have great potential for produce alumni who have diverse expertise and skills. This business model provides benefits to alumni in terms of economic independence, job creation, self-empowerment, dissemination of values and religious education, as well as community development and social empowerment. The alumni can develop a business that incorporates the principles of ethics, justice and social responsibility, thereby encouraging sustainable economic growth and improving the welfare of the surrounding community. However, there are challenges that need to be faced in implementing this business model, such as market competition, careful financial management, and fulfilling market needs that continue to grow. Therefore, an effective development strategy, collaboration with stakeholders, and empowering alumni are essential for business success and wider positive impact. Overall, the Islamic boarding school alumni business model is an innovative approach that combines religious values, education, and economic empowerment